Evolution of the US Arctic Policy - A. V. Borisov (Problemy Postsovetskogo Prostranstva, 2021)
The article examines the development of the US Arctic policy which is reflected in the US strategic documents. The author examines the evolution of doctrinal purposes from those focusing on environmental issues and regional cooperation to those focusing on logistics, security and military infrastructure. The evolution of the US strategic documents is considered in the context of the activities of such actors as Russia, Canada, China and a number of international organizations in the Arctic region. Contradictions and existing and prospective areas of cooperation are noted. The author shows the immutability of the US key strategic guidelines of the United States aimed at securing the status of an Arctic power for the United States and ensuring the promotion and protection of the US interests in the region.